The helical buckling analysis of coiled tubing in offshore pipelines. (17th February 2019) - Guan, Feng; Qin, Hua; An, Chen; Jiang, Qifeng; Liu, Shaohu; Ma, Weiguo; Yang, Ting; Wu, Jiwei
ABSTRACT: Buckling deformation of pipe in actual bore hole will limit the maximum running depth and is likely to further damage the drilling pipe, causing huge losses. Therefore, the buckling analysis of the pipe is necessary. In order to investigate the mechanical behaviour of coiled tubing (CT), a test bench including a vertical, a bending and a horizontal segments and an end-loading unit is designed. In this paper, the method of combined numerical calculation and experimental validation is used to study the inside-pipeline CT buckling. Based on the experimental investigation, the influence of induced torque on the helical buckling equation is analysed. In addition, by comparing the theoretical result and experimental result, the helical reverse phenomenon is carefully analysed. In the end, the maximum running depth for different CTs in different diameters and friction environments are also investigated, having an instructive significance to the actual operation and the choice of CT.